Resistance training in the young athlete - Myer, G. D.; Wall, E. J. (Operative techniques in Sports Medicine, 2006)
Concomitant with increasing participation in youth sports, there is a desire for young athletes to use resistance training to help them achieve peak performance. Recent evidence dispels the myths that weightlifting in children is dangerous as the result of growth plate injury risk and ineffective because children are unable to increase strength or muscle mass. Supervised resistance training currently is recognized to be safe and effective, and it also may reduce injury risk during sports participation in young athletes. In this review, we provide evidence-based guidelines to assist physicians when making recommendations to parents and coaches who wish to administer resistance training to young athletes.